2015
DOI: 10.1016/j.lungcan.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Dovitinib and erlotinib in patients with metastatic non-small cell lung cancer: A drug–drug interaction

Abstract: Introduction Erlotinib is a FDA approved small molecule inhibitor of epidermal growth factor receptor and dovitinib is a novel small molecule inhibitor of fibroblast growth factor and vascular endothelial growth factor receptor. This phase 1 trial was conducted to characterize the safety and determine the maximum tolerated dose of erlotinib plus dovitinib in patients with previously treated metastatic non-small cell lung cancer. Methods Escalating dose cohorts of daily erlotinib and dovitinib dosed 5 days on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…33,34 In this regard, a recent phase I trial testing the safety of erlotinib combined with the FGFR unselective inhibitor dovitinib in patients with NSCLC was terminated because of unacceptable toxicity. 35 In the present work, however, we have proposed combining EGFR inhibitors with a more selective FGFR1 inhibitor, hoping to result in a more favorable tolerability profile.…”
Section: Discussionmentioning
confidence: 97%
“…33,34 In this regard, a recent phase I trial testing the safety of erlotinib combined with the FGFR unselective inhibitor dovitinib in patients with NSCLC was terminated because of unacceptable toxicity. 35 In the present work, however, we have proposed combining EGFR inhibitors with a more selective FGFR1 inhibitor, hoping to result in a more favorable tolerability profile.…”
Section: Discussionmentioning
confidence: 97%
“…However, in a phase I study (NCT0151969), the combination of an EGFR TKI (erlotinib) with dovitinib (a multireceptor TKI with activity against FGFR1 and FGFR3) led to intolerable toxicity. 28 Therefore, it may be more feasible to consider combining EGFR inhibitors with more selective FGFR inhibitors currently in clinical development. Whether serial administration of these agents (i.e., an EGFR Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, predictions were based on its reversible IC 50 value only and suggested minor interactions with CYP3A4 substrates (≤1.3‐fold increases in AUC). Dovitinib is a strong CYP1A inducer and has markedly (by >90%) reduced the plasma exposures to the CYP1A marker substrate caffeine and to erlotinib, a CYP1A and CYP3A4 substrate, in human beings . No other interaction studies have hitherto been reported.…”
Section: Discussionmentioning
confidence: 99%